2008
DOI: 10.2495/dn080081
|View full text |Cite
|
Sign up to set email alerts
|

Fail safe design with crack stoppers and warners

Abstract: Trees attach thicker tree rings at overloaded places. This principle is mimicked here in order to delay crack initiation and propagation. Bulges are attached beside notches to reduce stress concentrations. The bulges have to be shape optimized so as to not cause notch stresses themselves. Brittle coating can act as a warner near notches. The crack stoppers are described by FEM and the result is verified by comparative fatigue testing of prototypes leading to up to 21 times longer fatigue life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It is demonstrated that those 'shirkers' do not contribute to the integrity of the structure by removing the unloaded region using the 'method of tensile triangles', published in . 3 In this paper, the finite-elementmethod (FEM), experiments and the so-called soft kill option-method (SKO) are used for further verification. SKO is a FEM-based method 5 that is inspired by osteoclasts in bones nibbling away non-loaded parts in the bony structure.…”
Section: Introductionmentioning
confidence: 99%
“…It is demonstrated that those 'shirkers' do not contribute to the integrity of the structure by removing the unloaded region using the 'method of tensile triangles', published in . 3 In this paper, the finite-elementmethod (FEM), experiments and the so-called soft kill option-method (SKO) are used for further verification. SKO is a FEM-based method 5 that is inspired by osteoclasts in bones nibbling away non-loaded parts in the bony structure.…”
Section: Introductionmentioning
confidence: 99%